Vidros óxidos de metais pesados contendo nanopartículas de metais de transição, para aplicações em fotônica - Montesso, Murilo (2012)
This work consists on the preparation and characterization of the optical, thermal and structural properties of glasses and nano-glass-ceramics based on heavy metal oxide glasses, containing different transition metal elements (Ni and Ag). We studied the follow vitreous compositions: 100-x(30SbPO4-50WO3-20PbO)-xNiCl2 (x= 0 - 10 % mol) and 100-x(SbPO4-WO3-PbO-4NiCl2)-xAgCl (x= 0 - 20 % mol). The glasses were prepared in platinum crucibles using the melting-quenching methodology. Thermal characterization was carried out using DSC technique, while the structural characterization was done using the X-ray diffraction, Infrared, and Raman spectroscopy. Optical properties were determined using UV-Vis, luminescence, Zscan and M-lines spectroscopy. Chemical analysis and the morphology of nanoparticles were studied by EDX and transmission electron microscopy, respectively. In order to induce controlled crystallization into the glassy matrix, heat treatments above Tg in both vitreous systems were performed. Samples containing only nickel have been studied by Luminescence and Z-Scan techniques to study the emission in the near infrared region and determine the nonlinear refractive index, respectively. Luminescence results obtained for the system 100-x(SbPO4-WO3-PbO)- xNiCl2 show infrared broad band emission into the range from 1.2 to 1.8 µm arising from Ni2+ transition in octahedral sites. Controlled thermal annealing leads to formation of NiO nanoparticles. Samples in the system 100-x(SbPO4-WO3-PbO- 4NiCl2)-xAgCl, when submitted to thermal annealing leads to crystallization of metallic silver nanoparticles with different sizes which is depending on the time of treatment. No changes in the optical spectra, concerning the Ni2+ transition were observed after thermal treatment.